Testing for enemy-mediated density-dependence in the mortality of seedlings: Field experiments with five Neotropical tree species - Gripenberg, S; Bagchi, R; Gallery, R; Freckleton, R; Narayan, L; Lewis, O (2014)
The coexistence of plant species in species-rich tropical forests can be promoted by specialised enemies acting in a negatively density-dependent manner. While survival of tropical tree seedlings is often negatively density-dependent, the causes have rarely been identified. We tested whether insects and plant pathogens cause density-dependent seedling recruitment and survival in five forest tree species in Belize, Central America. We manipulated densities of seeds or newly germinated seedlings in small (1 m2 or 0.25 m2) plots close to fruiting conspecific trees. Using a factorial design, we excluded enemies from subsets of the plots with fungicides and insecticides. Seed germination (for two species) and early seedling survival (for all species) were monitored at approximately weekly intervals for up to eight weeks, during the period when plants are likely to be most susceptible to natural enemies. In Terminalia amazonia, seed germination was negatively density-dependent and the proportion of seeds germinating increased when insects were excluded. However, the magnitude of the insecticide effect was independent of density. The only significant density effect for survival of young seedlings was in Acacia polyphylla; counter to expectation, seedling survival was higher at high densities. In a few cases pesticide application had a significant effect on seedling survival, but in only one case (Terminalia amazonia) was a significant pesticide × density interaction detected. Our results caution against generalising from studies conducted on a single species at a single time and place and illustrate the challenges of experimentally testing for enemy-mediated negative density-dependence. Experimental outcomes are likely to depend on the spatial scale at which the principal enemies disperse and respond to plant density, and the timescales over which they act. Gathering information on these variables will improve our understanding of the natural histories of tropical forest species and help inform the design of future experiments. © 2013 The Authors.